WRIPUB 2021
DOI: 10.46830/wrirpt.20.00006
|View full text |Cite
|
Sign up to set email alerts
|

A Pathway to Carbon Neutral Agriculture in Denmark

Abstract: Can the world meet growing demand for food while sharply reducing greenhouse gas emissions from agriculture – and without converting more forests into agriculture? In the World Resources Report: Creating a Sustainable Food Future, WRI set forth a challenging, global five-course menu of actions to do so. How should a country adapt this menu to its own agricultural context? A Pathway to Carbon Neutral Agriculture in Denmark answers this question for Denmark, a country whose major agricultural organizations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 146 publications
0
50
0
Order By: Relevance
“…Most developed countries agreed to implement the Paris Climate Accord, committing to reduce agricultural greenhouse gas emissions by 30% by 2050. They could be early adopters of BNI wheats in intensive production systems ( 52 ). From an agronomic perspective, the aim is to minimize nitrogen leakage, allowing for lower N fertilization without losing productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most developed countries agreed to implement the Paris Climate Accord, committing to reduce agricultural greenhouse gas emissions by 30% by 2050. They could be early adopters of BNI wheats in intensive production systems ( 52 ). From an agronomic perspective, the aim is to minimize nitrogen leakage, allowing for lower N fertilization without losing productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Realizing the full potential of BNI wheats, however, depends on a successful transfer of BNI trait (T3BL.3Ns b S) into elite varieties adapted to diverse agro-climatic conditions representative of wheat growing areas. In our view, this requires a major initiative by the global wheat research community, private sector, policy makers, and research funders ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., where beef consumption is the second highest in the world [ 25 ] and where beef accounts for nearly half of land-use and GHG emissions associated with diets [ 26 , 27 ], reducing red meat consumption could yield significant environmental benefits [ 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. An analysis from the World Resources Institute showed that reducing beef consumption to the world average level in regions such as the U.S. where beef consumption is above average could spare 300 million hectares of pasture [ 27 ], an area nearly the size of India.…”
Section: Introductionmentioning
confidence: 99%
“…There is a dire need to identify the sectors and later devise strategic planning to address the relevant threatening issues to the environment to combat climate change. Among these sectors, the agriculture sector remained a significant contributor to carbon emissions alone, generating a considerable amount of adverse emissions due to the use of traditional farming means, including the use of nitrogen-based fertilizers (Searchinger et al, 2019 ; Newton et al, 2020 ). In verily, this is a phenomenal source of adverse impacts on the global climate and environment (Searchinger et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%